Analysis of Model Transformations via Alloy - Anastasakis, Kyriakos; Bordbar, Behzad; Küster, Jochen (Proceedings of the workshop on Model-Driven Engineering, Verification and Validation (MoDeVVA 2007), Nashville, TN (USA))

Towards Model-Driven Unit Testing - Engels, Gregor; Güldali, Baris; Lohmann, Marc (Proceedings of the 2006 International Conference on Models in Software Engineering (MoDELS 2006))
The Model-Driven Architecture (MDA) approach for constructing software systems advocates a stepwise refinement and transformation process starting from high-level models to concrete program code. In contrast to numerous research efforts that try to generate executable function code from models, we propose a novel approach termed model-driven monitoring. On the model level the behavior of an operation is specified with a pair of UML composite structure diagrams (visual contract), a visual notation for pre- and post-conditions. The specified behavior is implemented by a programmer manually. An automatic translation from our visual contracts to JML assertions allows for monitoring the hand-coded programs during their execution. In this paper we present an approach to extend our model-driven monitoring approach to allow for model-driven unit testing. In this approach we utilize the generated JML assertions as test oracles. Further, we present an idea how to generate sufficient test cases from our visual contracts with the help of model-checking techniques.

Analysis of UML Activities with Dynamic Meta Modeling Techniques - Soltenborn, Christian; Engels, Gregor (Symposium "A Formal Semantics for UML" (satellite event of the MoDELS conference 2006), Genova (Italy))

Consistency of Business Process Models and Object Life Cycles - Ryndina, Ksenia; Küster, Jochen; Gall, Harald (Models in Software Engineering (1st Workshop on Quality in Modeling at MoDELS 2006, Genoa (Italy)))

On the Pitfalls of UML Activity Modeling - Schattkowsky, Tim; Förster, Alexander (Proceedings of the ICSE workshop on Modeling in Software Engineering (MISE 2007), Minneapolis, MN (USA))
With the introduction of new Petri net-like semantics for Activities in UML 2.0, these have become a complete language for modeling behavior. Thus, UML Activities are nowadays investigated for application in many areas from embedded systems to business process modeling. However, some issues have been discovered that currently seem to limit the practical applicability of Activities. In this paper, we present an overview of the identified semantic and syntactic problems, and point at possible solutions and directions for future research.

Strong spin–orbit interactions in carbon doped p-type GaAs heterostructures - Grbić, B.; Leturcq, R.; Ihn, T.; Ensslin, K.; Reuter, Dirk; Wieck, A.D. (Physica E: Low-dimensional Systems and Nanostructures)

Aharonov–Bohm oscillations in p-type GaAs quantum rings - Grbić, Boris; Leturcq, Renaud; Ihn, Thomas; Ensslin, Klaus; Reuter, Dirk; Wieck, Andreas D. (Physica E: Low-dimensional Systems and Nanostructures)

High sensitivity far-infrared detection by resonant inter-Landau-level scattering - Notthoff, C.; Lorke, A.; Reuter, Dirk (Physica E: Low-dimensional Systems and Nanostructures)

Aharonov–Bohm effect of quantum Hall edge channels - Giesbers, A.J.M.; Zeitler, U.; Reuter, Dirk; Wieck, A.D.; Biasiol, G.; Sorba, L.; Maan, J.C. (Physica E: Low-dimensional Systems and Nanostructures)

Magnetic-field-induced modification of the wave-functions in InAs quantum dots - Lei, W.; Wibbelhoff, O.; Notthoff, C.; Marquardt, B.; Reuter, Dirk; Wieck, A.D.; Lorke, A. (Physica E: Low-dimensional Systems and Nanostructures)

Influence of In0.15Ga0.85As capping layers on the electron and hole energy levels of InAs quantum dots - Richter, Mirja; Reuter, Dirk; Duboz, Jean-Yves; Wieck, Andreas D. (Physica E: Low-dimensional Systems and Nanostructures)

Capacitance–voltage spectroscopy of post-growth annealed InAs quantum dots - Reuter, Dirk; Roescu, Razvan; Mehta, Minisha; Richter, Mirja; Wieck, A.D. (Physica E: Low-dimensional Systems and Nanostructures)

Site-selective growth of self-assembled InAs quantum dots on focused ion beam patterned GaAs - Mehta, M.; Reuter, Dirk; Melnikov, A.; Wieck, A.D.; Remhof, A. (Physica E: Low-dimensional Systems and Nanostructures)

Quantum dots as tunable scatterers for 2D- and 1D-electron systems - Marquardt, Bastian; Russ, Marco; Lorke, Axel; Meier, Cedrik; Reuter, Dirk; Wieck, Andreas D. (Physica E: Low-dimensional Systems and Nanostructures)

A comparison: 2D electron- and hole systems in the fractional quantum Hall regime - Hadzibrahimovic, Adriana; Dethlefsen, Annelene F.; Reuter, Dirk; Wieck, Andreas D.; Tranitz, Hans-Peter; Wegscheider, Werner; Haug, Rolf J. (Physica E: Low-dimensional Systems and Nanostructures)

Hot-electron bend resistance in a ballistic GaAs/AlGaAs cross junction - Wiemann, M.; Cetinkaya, A.; Wieser, U.; Kunze, U.; Reuter, Dirk; Wieck, A.D. (Physica E: Low-dimensional Systems and Nanostructures)

Magneto-ballistic effects in non-centrosymmetric GaAs/AlGaAs cross junctions - Wieser, U.; Knop, M.; Kunze, U.; Reuter, Dirk; Wieck, A.D. (Physica E: Low-dimensional Systems and Nanostructures)

Magneto-optical probing of weak disorder in a two-dimensional hole gas - Bryja, Leszek; Wójs, Arkadiusz; Misiewicz, Jan; Potemski, Marek; Reuter, Dirk; Wieck, Andreas (Physical Review B)

Spin-controlled LEDs and VCSELs - Hövel, S.; Gerhardt, N. C.; Brenner, C.; Hofmann, M. R.; Lo, F.-Y.; Reuter, Dirk; Wieck, A. D.; Schuster, E.; Keune, W. (physica status solidi (a))

Subsecond Spin Relaxation Times in Quantum Dots at Zero Applied Magnetic Field Due to a Strong Electron-Nuclear Interaction - Oulton, R.; Greilich, A.; Verbin, S. Yu.; Cherbunin, R. V.; Auer, T.; Yakovlev, D. R.; Bayer, M.; Merkulov, I. A.; Stavarache, V.; Reuter, Dirk; Wieck, A. D. (Physical Review Letters)

Sequential and cotunneling behavior in the temperature-dependent thermopower of few-electron quantum dots - Scheibner, R.; Novik, E. G.; Borzenko, T.; König, M.; Reuter, Dirk; Wieck, A. D.; Buhmann, H.; Molenkamp, L. W. (Physical Review B)

Exciton fine structure inInGaAs∕GaAsquantum dots revisited by pump-probe Faraday rotation - Yugova, I. A.; Greilich, A.; Zhukov, E. A.; Yakovlev, D. R.; Bayer, M.; Reuter, Dirk; Wieck, A. D. (Physical Review B)

Robust manipulation of electron spin coherence in an ensemble of singly charged quantum dots - Greilich, A.; Wiemann, M.; Hernandez, F. G. G.; Yakovlev, D. R.; Yugova, I. A.; Bayer, M.; Shabaev, A.; Efros, Al. L.; Reuter, Dirk; Wieck, A. D. (Physical Review B)

Universal behavior of the electrongfactor inGaAs∕AlxGa1−xAsquantum wells - Yugova, I. A.; Greilich, A.; Yakovlev, D. R.; Kiselev, A. A.; Bayer, M.; Petrov, V. V.; Dolgikh, Yu. K.; Reuter, Dirk; Wieck, A. D. (Physical Review B)

Charge and spin dynamics in a two-dimensional electron gas - Pugžlys, A; Rizo, P J; Ivanin, K; Slachter, A; Reuter, Dirk; Wieck, A D; Wal, C H van der; Loosdrecht, P H M van (Journal of Physics: Condensed Matter)

Magnetic and structural properties of Gd-implanted zinc-blende GaN - Lo, F.-Y.; Melnikov, A.; Reuter, Dirk; Wieck, A. D.; Ney, V.; Kammermeier, T.; Ney, A.; Schörmann, J.; Potthast, S.; As, D. J.; Lischka, K. (Applied Physics Letters)

Experimental imaging and atomistic modeling of electron and hole quasiparticle wave functions inInAs∕GaAsquantum dots - Bester, G.; Reuter, Dirk; He, Lixin; Zunger, A.; Kailuweit, P.; Wieck, A. D.; Zeitler, U.; Maan, J. C.; Wibbelhoff, O.; Lorke, A. (Physical Review B)

Focused ion beam implantation induced site-selective growth of InAs quantum dots - Mehta, M.; Reuter, Dirk; Melnikov, A.; Wieck, A. D.; Remhof, A. (Applied Physics Letters)

Nuclei-Induced Frequency Focusing of Electron Spin Coherence - Greilich, A.; Shabaev, A.; Yakovlev, D. R.; Efros, Al. L.; Yugova, I. A.; Reuter, Dirk; Wieck, A. D.; Bayer, M. (Science)

Measurement of the specific heat of a fractional quantum Hall system - Schulze-Wischeler, F.; Zeitler, U.; v. Zobeltitz, C.; Hohls, F.; Reuter, Dirk; Wieck, A. D.; Frahm, H.; Haug, R. J. (Physical Review B)

Systematic study of carrier correlations in the electron-hole recombination dynamics of quantum dots - Berstermann, T.; Auer, T.; Kurtze, H.; Schwab, M.; Yakovlev, D. R.; Bayer, M.; Wiersig, J.; Gies, C.; Jahnke, F.; Reuter, Dirk; Wieck, A. D. (Physical Review B)

The Influence of Device Geometry on Many-Body Effects in Quantum Point Contacts: Signatures of the 0.7 Anomaly, Exchange and Kondo - Koop, E. J.; Lerescu, A. I.; Liu, J.; van Wees, B. J.; Reuter, Dirk; Wieck, A. D.; van der Wal, C. H. (Journal of Superconductivity and Novel Magnetism)

CYCLOTRON RESONANCE IN COUPLED BILAYERS IN HIGH MAGNETIC FIELDS - GÜRTLER, A.; ZEITLER, U.; MAAN, J. C.; Reuter, Dirk; WIECK, A. D. (International Journal of Modern Physics B)

Aharonov-Bohm Oscillations in the Presence of Strong Spin-Orbit Interactions - Grbić, Boris; Leturcq, Renaud; Ihn, Thomas; Ensslin, Klaus; Reuter, Dirk; Wieck, Andreas D. (Physical Review Letters)

Spin Coherence of Holes inGaAs/(Al,Ga)AsQuantum Wells - Syperek, M.; Yakovlev, D. R.; Greilich, A.; Misiewicz, J.; Bayer, M.; Reuter, Dirk; Wieck, A. D. (Physical Review Letters)

Evidence for the Luttigger liquid density of states in transport across the incompressible stripe at fractional filling factors - Deviatov, E. V; Kapustin, A. A; Dolgopolov, V. T; Lorke, A; Reuter, Dirk; Wieck, A. D (Europhysics Letters (EPL))

Hole levels in InAs self-assembled quantum dots - Blokland, J. H.; Wijnen, F. J. P.; Christianen, P. C. M.; Zeitler, U.; Maan, J. C.; Kailuweit, P.; Reuter, Dirk; Wieck, A. D. (Physical Review B)

Bildungsstandards in der Berufsbildung – Kompetenzen messen auf Basis des Rasch-Modells. Konzeption und Erprobung der Messung - Beutner, Marc (Paderborner Forschungs- und Entwicklungswerkstatt)

Die Förderung interkulturellen Verständnis in der beruflichen Bildung - Beutner, Marc (Fremde Kulturen verstehen – fremde Kulturen lehren. Theorie und Praxis der Vermittlung interkultureller Kompetenz)

Stierstorfer, K. / L. Volkmann (Hg.): Kulturwissenschaft Interdisziplinär - Tönnies, Merle (Anglistik. International Journal of English Studies)

Die Grundlagen der Mechanismus-Design-Theorie - Hehenkamp, Burkhard (Wirtschaftsdienst)

Line narrowing and hole burning within the homogeneous linewidth: a new wave-mixing effect in two-level systems - Förstner, Jens; Knorr, A.; Lindberg, M.; Koch, S. W. (Optics Letters)
The interaction of strong low-area pulses with two-level systems shows absorption line narrowing and hole burning within the homogeneous linewidth as a result of nonlinear wave mixing. The wave mixing results from the two-level electronic saturation nonlinearity and occurs, depending on the sign of the pulse area, as a strong absorption enhancement or gain at the transition frequency of the two-level system for resonant excitation.
Keywords: tet_topic_polariton

Outsourcing von Personalfunktionen - Alewell, Dorothea; Bähring, Katrin; Canis, Anne; Hauff, Sven; Thommes, Kirsten (Motive und Erfahrungen im Spiegel von Experteninterviews)

Vertikale Entflechtung netzgebundener Industrien: Kosten und Nutzen aus ökonomischer Sicht - Haucap, Justus; Heimeshoff, Ulrich; Uhde, André (Gesellschaft für öffentliche Wirtschaft)
Die in den letzten 25 Jahren weltweit und in Europa in den letzten zehn Jahren forcierte Liberalisierung der Telekommunikationsbranche stellt ein bemerkenswertes Beispiel für den erfolgreichen Wandel ordnungspolitischer Rahmenbedingungen dar. Die Erfolge dieser Reformprozesse sowie die daraus resultierenden institutionellen Lernprozesse waren auch für die übrigen netzgebundenen Industrien wie z.B. Energiewirtschaft, Bahn oder Post wegweisend. Thema dieses Aufsatzes ist das Spannungsfeld zwischen der Vermeidung von Diskriminierungsanreizen durch vertikale Separierung, möglichen Effizienzgewinnen und adäquaten Investitionsanreizen. Im Folgenden werden sowohl theoretische Grundlagen netzgebundener Industrien im Allgemeinen als auch theoretische Argumente für oder gegen eine vertikale Integration netzgebundener Industrien diskutiert. Die theoretischen Argumente werden anschließend beispielhaft auf den Bahnsektor, die Energiewirtschaft sowie die Wasserwirtschaft angewendet.

Managing Credit Risk with Credit Derivatives - Broll, Udo; Gilroy, Bernard Michael; Lukas, Elmar (Annals of Financial Economics)

Managing Credit Risk with Credit Derivatives - Broll, Udo; Gilroy, Bernard Michael; Lukas, Elmar (Annals of Financial Economics)

A Different View to Atypical Work: Interim Management. - Kabst, Rüdiger (Korean Journal of Economics.)

Determinanten des Downsizings: Eine empirische Analyse mit den Daten des Cranfield Project on International HRM. - Weller, I; Kabst, Rüdiger (Die Betriebswirtschaft (DBW).)

Scenario-based scales measuring cultural orientations of business owners. - Koenig, C; Steinmetz, Holger; Frese, M; Rauch, A; Wang, Z M (Journal of Evolutionary Economics.)

A Scalable and Flexible Infrastructure Framework For Addressing Spam - Schryen, Guido (Proceedings of IPSI International Conference on Advances in the Internet, Processing, Systems, and Interdisciplinary Research)